2021
DOI: 10.3390/diagnostics11091685
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behavior Related to COVID-19 Testing: A Rapid Scoping Review

Abstract: Testing programs for COVID-19 depend on the voluntary actions of members of the public for their success. Understanding people’s knowledge, attitudes, and behavior related to COVID-19 testing is, therefore, key to the design of effective testing programs worldwide. This paper reports on the findings of a rapid scoping review to map the extent, characteristics, and scope of social science research on COVID-19 testing and identifies key themes from the literature. Main findings include the discoveries that peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 79 publications
(384 reference statements)
1
39
0
1
Order By: Relevance
“…This qualitative study moves beyond individual perceptions of COVID-19 testing and underscores the substantial impact of upstream, structural disparities on the individual level experience of COVID-19, from infection to morbidity to mortality as well as on access to information and resources and uptake of preventive behaviors such as mask wearing and social distancing ( 19 , 34 ). While we found that stakeholders expressed barriers and facilitators to testing at each level of the Social Ecological Model—individual, interpersonal, organization, community, and societal—the solutions for addressing these influences depend on institutional and governmental changes ( 32 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This qualitative study moves beyond individual perceptions of COVID-19 testing and underscores the substantial impact of upstream, structural disparities on the individual level experience of COVID-19, from infection to morbidity to mortality as well as on access to information and resources and uptake of preventive behaviors such as mask wearing and social distancing ( 19 , 34 ). While we found that stakeholders expressed barriers and facilitators to testing at each level of the Social Ecological Model—individual, interpersonal, organization, community, and societal—the solutions for addressing these influences depend on institutional and governmental changes ( 32 ).…”
Section: Discussionmentioning
confidence: 90%
“…The structural barriers identified, such as inadequate safety net policies for workers, immigration policies, and transportation, have lasting and multiplicative impacts at the individual level and may serve as launch points for next steps and future translational research. While prior studies have explored barriers and facilitators to COVID-19 testing among the general population or among one specific sub-population ( 18 , 19 , 36 , 37 ), our study drew on a diverse array of perspectives to understand barriers and facilitators specific to several underserved populations (e.g., individuals experiencing homelessness, immigrant populations, individuals living in multigenerational households). This data better informed how CHCs and community partners could apply targeted approaches most relevant to specific populations disproportionally impacted by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers identified in this research included patient choice and the unpredictable nature of maternity admissions. Elsewhere, the general population has commented on reasons for declining testing include that sample extraction is unpleasant, fear of the consequences of a positive result and test results taking too long [ 13 ], [ 14 ]. Our research found that only 27% of respondents’ hospitals test birth partners.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the ubiquity of testing in high-income countries afflicted by high case rates only makes the scarcity of testing systems in many low-and middle-income countries starker (Kelley et al 2020;Munharo et al 2020). Such testing disparities are also reflected in the distribution of social research into COVID-19 testing, with the vast majority of studies on the topic focusing on highincome countries in the Global North (Bevan et al 2021). Moreover, the fact that COVID-19 has brought the ethics and politics of medical testing to public attention does not mean medical testing was not already 'everywhere' before-only that, perhaps, it had less public visibility as a social, political, economic, and ethical 'problem'.…”
mentioning
confidence: 99%